Al-Washliyah Business Management Strategy Analysis of North Sumatra Al-Washliyah - Burhanuddin; Ratna Sari Dewitra; Ayu Ulandari (Journal Of Management Analytical and Solution (JoMAS), 2022)
Al Jam'iyatul Washliyah is an Islamic community organization that was born on November 30, 1930 in Medan, North Sumatra. This study aims to explore the management strategy of Al Jam'iyatul Washliyah's charitable business. This research is classified as field research. That way the object of research is an object in the field that is able to provide information about research studies. This research shows that, on the one hand, Al-Washliyah's charitable om88 efforts already exist in carrying out their functions in the organization. On the other hand, the Al-Washliyah organization has not been able to fully overcome the problems of managing its business charity. The main finding produced in this study, is that the organization has not been able to enforce regulations according to the demands of AD/ART AW, as a result, Al-Washliyah's charitable efforts have not been able to fully regulate organization, assets and administrative order.